Řízení rizik v oblasti BOZP ve výrobním procesu - Podaný, Tomáš (Vysoké učení technické v Brně. Ústav soudního inženýrství, 2019)
Diplomová práce zkoumá a řeší problematiku rizik ve výrobní společnosti z pohledu bezpečnosti a ochrany při práci (BOZP). První část diplomové práce osahuje problematiku procesu BOZP v obecné a teoretické rovině. Dále práce postupuje na základě analýz a z nich identifikuje rizika. Pro zjištěná rizika jsou poté na konkrétních příkladech v modelové firmě navržena řešení, která je buďto úplně odstraní nebo alespoň sníží. V závěrečné části diplomová práce shrnuje výstupy a uvádí doporučení.

The diploma thesis focuses on the issues of risks in manufacture company from the prospective occupational health and safety at work (OHS). The first part of the diploma thesis contains theoretical background of the OHS process then proceeds with analysis and corresponding risks identification. There are suggested solutions on the concrete examples in the model company which completely eliminate discovered risks or at least reduce them. The final part of the diploma thesis summarizes conclusions and presents recommendations.
Risk Management in OSH in the Manufacturing Process
Keywords: Bezpečnost a ochrana zdraví při práci; rizika; metody; analýza; návrhy; Occupational and safety and health; risks; methods; analysis; suggestions